Editorial Foreword - Idealogy Journal: Vol. 6, No. 2, September 2021 - Ab Gani, Muhamad Abdul Aziz; Ramli, Ishak; Yahaya, Mohamad Hafiz; Taharuddin, Nurul Shima; Md Nazri, Haslinda; Rosman, Muhammad Redza; Nazrin, Nizar (Idealogy Journal, 2021)
We are very pleased that IDEALOGY JOURNAL, Journal of Arts and Social Science is presenting its 6th volume and 2nd issue. We are also very excited that the journal has been attracting papers from a variety of advanced and emerging countries such as Indonesia, Pakistan, Saudi Arabia, Bangladesh, etc. The variety of submissions from such countries will help the aimed global initiatives of the journal. We are also delighted that the researchers from the Arts and Social Science fields demonstrate an interest to share their research with the readers of this journal. This issue of Journal of Arts and Social Science contains five outstanding articles which shed light on contemporary research questions in arts and social science fields. All the 13 papers of this issue studies the are discussing about culture, art, design, technology, creativity and art & design innovation. There is also discussion about art, design and culture in various area. In this issue, most of the articles are discussing on the topic of arts and the social science. In social science it is very important to have a combination of different discipline to ensure the survival of knowledge. By combining knowledge from different fields, it could produce new innovation that could lead to solutions to many important problems or issues. Hence Idealogy Journal of Arts and Social Sciences is a platform for many fields of knowledge to share research findings as well as literatures. As we were aware at the first issue, a journal needs commitment, not only from editors but also from editorial boards and the contributors. Without the support of our editorial board, we would not dare to start and continue. Special thanks, also, go to the contributors of the journal for their trust, patience and timely revisions. We continue welcome article submissions in all fields of arts and social sciences.